Iranian pre-university English teachers' perceptions and attitudes towards the Iranian national university entrance exam: a washback study - Mahmoudi, Leila; Abu Bakar, Kamariah (Australian International Academic Centre, 2013)
The washback effect of high-stakes tests has been explored in different countries and various educational contexts. Washback generally refers to the influence of testing on teaching and learning (Alderson & Wall, 1993). This paper which is a part of a larger study seeks to report the perceptions and attitudes of Iranian pre-university English teachers towards the effect of Iranian National University Entrance Exam (hereafter the INUEE) on teachers’ English teaching and learners’ English learning. The participants were 6 female pre-university English teachers from two pre-university schools in the city of Ahwaz, Iran. To investigate their perceptions and attitudes towards the INUEE, a validated questionnaire was administered to the teachers and a semi-structured interview was also conducted in order to gain richer information, and to shed more light on the data collected through their questionnaires. The respondents answered questions on whether the test motivated the students to learn English, whether the INUEE evaluated students’ academic knowledge, etc. The descriptive and qualitative analysis of the data revealed that teachers’ perceptions towards the test were mixed. Two teachers held positive views about the test and four other teachers held negative perceptions about this high-stakes test. The findings of this study could be pedagogically significant to policy-makers, test designers, teachers, and students.